Analysis of Raw Material Control and Planning on Line Assy Sunflower with Material Requirement Planning Method at PT Techno Indonesia - Miftakul Huda; Nani Hartati (Journal of Research in Business, Economics, and Education, 2021)
PT Techno Indonesia is a local company engaged in injection molding for electronic and automotive parts. This study describes the control and planning of raw materials for sub-assy products, namely Paper Eject Assy Sunflower for the period July - December 2019. Problems that occur include the accumulation of raw material inventories so that it has the potential to harm the company because the inventory costs should be allocated to other investments. This study aims to determine: (1) (1) The best forecast to estimate the need for new materials per period that will come to PT Techno Indonesia. (2). Planning and controlling raw material inventory using the Material Requirement Planning (MRP) method at PT Techno Indonesia. In this study determined the planning of controlling raw materials with MRP using the calculation of the modeling of material procurement using the Lot For Lot (LFL) and Fixed Order Quantity (FOQ) methods. The results of this study prove that the best forecasting is applied in PT Techno Indonesia, the forecasting method uses Weighted Moving Average and Material Requirement Planning (MRP) using the Lot Fot Lot method.